2021
DOI: 10.3389/fimmu.2020.627424
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles as Inflammatory Drivers in NAFLD

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent chronic liver disease in most parts of the world affecting one-third of the western population and a growing cause for end-stage liver diseases such as hepatocellular carcinoma (HCC). Majorly driven by obesity and diabetes mellitus, NAFLD is more of a multifactorial disease affected by extra-hepatic organ crosstalk. Non-alcoholic fatty liver (NAFL) progressed to non-alcoholic steatohepatitis (NASH) predisposes multiple complications such as fibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 99 publications
1
44
0
4
Order By: Relevance
“…In the context of inflammation it was recently demonstrated that miRNA- let-7e-5p, contained in EVs derived from hepatocytes enhances lipid accumulation in adipocytes [ 30 ]. Moreover, EV-miR-192-5p from hepatocytes activate macrophages and increase IL-6 and TNF-α expression, promoting inflammation in NAFLD, summarized in [ 31 ]. Thus, beyond demonstrating a potential role of EV as biomarkers in patients receiving TACE our data also provide pathophysiological insights into different processes determining the prognosis of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of inflammation it was recently demonstrated that miRNA- let-7e-5p, contained in EVs derived from hepatocytes enhances lipid accumulation in adipocytes [ 30 ]. Moreover, EV-miR-192-5p from hepatocytes activate macrophages and increase IL-6 and TNF-α expression, promoting inflammation in NAFLD, summarized in [ 31 ]. Thus, beyond demonstrating a potential role of EV as biomarkers in patients receiving TACE our data also provide pathophysiological insights into different processes determining the prognosis of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of EV isolated from high fat diet (HFD) mice into normal fed mice have been shown to result in exacerbation of hepatic steatosis and accumulation of activated myeloid cells in the liver through the release of chemotactic EV ( Ibrahim et al, 2016 ). In addition to hepatocyte-derived EV, extra-hepatic EV have also been implicated in the progression of NAFLD, NASH and associated fibrosis ( Srinivas et al, 2021 ). Due to their ability to carry signal from one cell type to another, they can activate or modulate target cell responses and are therefore an emerging therapeutic targets in NAFLD and NASH.…”
Section: Soluble Mediators In Liver Fibrosismentioning
confidence: 99%
“…Hepatocytes are the main cell type of the liver, accounting for 80% of the liver volume. Studies on mouse models and human subjects with NASH showed that hepatocytes are the main contributors to the elevated levels of circulating EVs ( Srinivas et al, 2020 ). Therefore, hepatocyte-derived EVs may play a key role in the pathogenesis and progression of NAFLD.…”
Section: Evs In the Pathogenesis Of Ald And Nafldmentioning
confidence: 99%